2014
DOI: 10.17795/jjcdc-21702
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Self-Management Programs on Self-Efficacy in Patients With Sickle Cell Disease

Abstract: BackgroundSickle cell patients suffer from many physical, psychological, and social problems that can affect their quality of life. To deal with this chronic condition and manage their disease and prevent complications associated with the disease, they must learn skills and behaviours. The aim of this study was to determine the effectiveness of self-management programs on quality of life in these patients.Material and MethodsSamples of this quasi-experimental study, which included 69 patients with sickle cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 48 publications
0
27
0
2
Order By: Relevance
“…They studied the effect of self-care programs on the self-efficacy of anemia sickle cell patients and concluded that self-care programs has a positive effect on their self-efficacy so that the self-efficacy, which was at a moderate level prior to intervention, increased after intervention (37). Moreover, Cashaw conducted a quasi-experimental study on a group to assess the effect of self-managing based on behavioral intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They studied the effect of self-care programs on the self-efficacy of anemia sickle cell patients and concluded that self-care programs has a positive effect on their self-efficacy so that the self-efficacy, which was at a moderate level prior to intervention, increased after intervention (37). Moreover, Cashaw conducted a quasi-experimental study on a group to assess the effect of self-managing based on behavioral intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Researches show that those individuals who trust their abilities actively participate in health programs promoting health level (16). Increased drug consumption, better relations with therapy team and promotion of health variables are among the positive outcomes of self-efficacy programs (17). In chronic diseases, training is a special part of care program by which patients actively participate in their health care programs and this, in turn, results in better interaction with clients.…”
Section: Introductionmentioning
confidence: 99%
“…95,96 Quality of life in SCD has been reported using the SF-36. 97,98 Unfortunately, behavioral change promoted by CHW does not guarantee quiescent symptoms of SCD, even with complete adherence to care plans. 21–24 …”
Section: Evaluating the Impact Of Community Health Workers On Sickle mentioning
confidence: 99%
“…Self-management programs are designed to help patients determine their needs and problems, and to assist them to overcome these (25). Although there is evidence indicating that self-management improves health outcomes in SC patients and patients with other chronic diseases (25)(26)(27)(28), little research has examined the implementation of such programs in reduction of pain, fatigue, depression, anxiety, and stress in patients with SCD.…”
Section: Introductionmentioning
confidence: 99%